Don't make me think : - Krug, Steve (New Riders, 2006)
Five years and more than 100,000 copies after it was first published, it's hard to imagine anyone working in Web design who hasn't read Steve Krug's "instant classic" on Web usability, but people are still discovering it every day. In this second edition, Steve adds three new chapters in the same style as the original: wry and entertaining, yet loaded with insights and practical advice for novice and veteran alike. Don't be surprised if it completely changes the way you think about Web design.